Perilaku Seks Beresiko HIV/AIDS Pada Anak Buah Kapal di Pelabuhan Hurnala Tulehu - Andi Rosmawati FR; Henry Setyawan Susanto; Suharyo Hadisaputro (Universitas Pahlawan Tuanku Tambusai, 2023)
Human Immunodeficiency Virus (HIV) is an RNA class virus that specifically attacks immunity or the immune system which then causes Acquired Immune Defiency Syndrome (AIDS). AIDS is a collection of symptoms of diseases that occur due to a decrease in the immune system caused by HIV. HIV kills patients slowly by infecting blood cells that play a role in the immune system so that these blood cells no longer function. ABK is a group that is a profession with a high level of mobility. The purpose of this study was to determine the relationship between condom use. The study aims to determine the relationship between attitudes, encouragement of women sex peddlers (WPS), condom use, and length of docking with sex behavior at risk of HIV / AIDS in ABK. The method used is observational analytic, with a cross sectional study design. The population is all crew whose ships dock and/or dock in the area of Hurnal Tulehu Port. Sampling using a simple random sampling method with a sample size of 370 people. The data analysis carried out was univariate and bivariate with chi square test and logistic regression test. The results of the study obtained variables related to sexual behavior at risk of HIV / AIDS were attitude (p = 0.005), WPS drive (p = 0.004), condom use (p = 0.002) and length of docking (p = 0.002. While the variable that is not related to sexual behavior at risk of HIV / AIDS is the variable level of education (p = 0.941). Of all related variables, a logistic regression test was carried out and the results were the variables of condom use that were most associated with HIV/AIDS risk sexual behavior in ABK (p = 0.051). The conclusion of the study is that there is a relationship between attitudes, WPS encouragement, condom use with and length of berthing ship with sexual behavior at risk of HIV / AIDS in fishermen whose ships dock at Hurnala Tulehu Port.